Gambaran Kesejahteraan Spiritual Pasien Gagal Ginjal Kronis yang Menjalani Hemodialisis - Frilisa J. Hi. Syafi; Ike Wuri Winahyu Sari (PSIK FKKMK UGM, 2022)
Background: Spiritual is one of the significant aspects in the concept of comprehensive nursing care. The broad variation of spiritual well-being and the limited number of research on spiritual well-being of patients with chronic kidney failure undergoing hemodialysis become the background of this research.Objective: To identify the spiritual well-being of patients undergoing hemodialysis.Method: The study used descriptive-analytic design. The sample was using purposive sampling technique with 62 patients with chronic kidney failure undergoing hemodialysis at RSUD Panembahan Senopati Bantul. Data was compiled through the valid and reliable Spiritual Well-Being Scale (SWBS) questionnaire. Data analysis consisted of univariate and bivariate (One-way ANNOVA and Unpaired T-test).Result: The measured respondents’ spiritual well-being was reached score of 91,58+10,47 within the range of 20-120. Based on the respondents’ characteristics, there is no difference of spiritual well-being based on age (p=0,691), gender (p=0,355), marital status (p=0,107), employment status (p=0,141), level education (p=0,141) and length of time of hemodialysis (p=0,300).Conclusion: The spiritual well-being of patients with chronic kidney failure undergoing hemodialysis at RSUD Panembahan Senopati Bantul was at the moderate level. There was not any significant difference of spiritual well-being based on respondents’ characteristics. Efforts to help patients obtain spiritual well-being through therapeutic communication, empathy, and facilitating patients to express spirituality are necessary. ABSTRAKLatar belakang: Spiritual merupakan salah satu aspek penting dalam konsep pelayanan keperawatan yang komprehensif. Beragamnya kesejahteraan spiritual dan sedikitnya penelitian mengenai gambaran kesejahteraan spiritual pasien Gagal Ginjal Kronis (GGK) yang menjalani hemodialisis mendorong penelitian ini untuk dilakukan.Tujuan: Penelitian ini bertujuan untuk mengetahui gambaran kesejahteraan spiritual pasien GGK yang menjalani hemodialisis.Metode: Desain penelitian yang digunakan yaitu deskriptif-analitik. Teknik pengambilan sampel menggunakan purposive sampling dengan besar sampel 62 pasien GGK yang menjalani hemodialisis di RSUD Panembahan Senopati Bantul. Pengumpulan data menggunakan kuesioner Spiritual Well-Being Scale (SWBS) yang telah valid dan reliabel. Analisis data terdiri atas univariat dan bivariat (uji One-way ANNOVA dan uji t tidak berpasangan).Hasil: Kesejahteraan spiritual responden bernilai 91,58±10,47 dalam rentang skor 20-120. Berdasarkan karakteristik reponden, tidak ada perbedaan kesejahteraan spiritual berdasarkan usia (p=0,691), jenis kelamin (p=0,355), status pernikahan (p=0,107), status pekerjaan (p=0,141), tingkat pendidikan (p=0,549), dan lama hemodialisis (p=0,300).Simpulan: Kesejahteraan spiritual pasien GGK yang menjalani hemodialisis di RSUD Panembahan Senopati Bantul pada tingkat sedang. Tidak ada perbedaan bermakna kesejahteraaan spiritual berdasarkan karakteristik responden. Upaya untuk membantu pasien mencapai kesejahteraan spiritual yang tinggi melalui komunikasi terapeutik, empati, dan memfasilitasi pasien untuk mengekspresikan spiritual perlu dilakukan.